Reading Comprehension Strategies Used by Students in Different Grades at MA Darul Ishlah (Al-Azhaar Boarding School Lubuklinggau) - Yunita Antasari; Dedi Sofyan; Azwandi Azwandi (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2021)
This study aimed to find out and investigate the use of reading strategies used by students in different grades of MA Darul Ishlah (Al-Azhaar Boarding School Lubuklinggau). The study employed a mixed method (quantitative and qualitative). The total number of the participants in this study was 108 students which come from class X is 53 students, class XI is 25 students, and the last class XII is 30 students. The instruments of this research were questionnaire and interview. The data were analyzed by using percentage formula. The major findings are, first, all students in different grades were medium in level of use for all the strategies. Second, they only used some strategy in reading comprehension, because there are some strategy was difficult for them to apply in reading comprehension and the strategy was not teach explicitly. For instance, in the first grade students in global reading strategy rarely used memorized, read aloud, guessing, and summary. Meanwhile, While, the most frequently reading strategy used by students in different grade is global reading strategy, then following by problem-solving reading strategy and the last is support reading strategy.